THE EFFECTIVENESS OF USING CHROMEBOOKS AS LEARNING MEDIA IN PAI AND CHARACTER EDUCATION ASSESSMENT ACTIVITIES - Eva Susanti; Nurlaili; Desy Eka Citra Dewi (Universitas Islam Negeri Mataram, 2025)
This study aims to evaluate the effectiveness of using Chromebooks as a learning medium in the PAI (Islamic Education) and Character Education assessment activities at SDN 90 Seluma, Bengkulu Province. The research adopts a mixed-method approach, combining quantitative and qualitative data. The research results indicate that using Chromebook media in these assessment activities has proven effective. Quantitative data shows that the Chromebook’s effectiveness is reflected in high accessibility (84%), interactivity (85%), and real-time feedback (84%). Meanwhile, in the PAI and Character education assessments, the ability to analyse data reached 81.2%, and personalisation and flexibility were at 79.52%. Qualitative data further support these findings, demonstrating that Chromebook media allows for efficient, smooth, and interactive assessments, significantly enhancing student motivation. The study concludes that Chromebooks are an effective tool for improving the quality of learning and assessment in modern education